Diversity of fruit bats (Pteropodidae) and their ectoparasites in Batuputih Nature Tourism Park, Sulawesi, Indonesia - MEIS NANGOY; TILTJE RANSALELEH; HANDRY LENGKONG; Roni Koneri; ALICE LATINNE; RANDALL C. KYES (Society for Indonesian Biodiversity, 2021)
Abstract. Nangoy M, Ransaleleh T, Lengkong H, Koneri R, Latinne A, Kyes RC. 2021. Diversity of fruit bats (Pteropodidae) and their ectoparasites in Batuputih Nature Tourism Park, Sulawesi, Indonesia. Biodiversitas 22: 3075-3082. Bats play an important role in the ecosystem as pollinators, seed dispersers, and predators, therefore, this study aims to identify the diversity of fruit bat species and ectoparasites at Batuputih Nature Tourism Park, Sulawesi, Indonesia. The study was conducted from May to July 2019, and carried out in three different habitats, namely primary and secondary forest, as well as agricultural land. Besides, the bats were caught using a mist net while the ectoparasites were collected and identified using morphological criteria. A total of 253 bats were sampled representing 10 species (all belonging to the family Pteropodidae) namely Cynopterus brachyotis (24.90%), C. luzoniensis (9.88%), Dobsonia exoleta (1.19%), Macroglossus minimus (3.16%), Nictymene cephalotes (4.75%), N. minutus (0.79%), Rousettus amplexicaudatus (17%), R. celebensis (20.95%), Thoopterus nigrescens (17%), and Thoopterus sp. (0.4%). Cynopterus brachyotis was the most abundant species (n = 63). Meanwhile, a total of 479 ectoparasites were collected and identified as belonging to three families, namely Nycteribiidae, Streblidae, and Spinturnicidae. Nycteribiidae (genus Leptocyclopodia) was the most abundant ectoparasite taxa (n= 475) while the highest mean abundance and intensity were observed for the genus Thoopterus and Rousettus. This study provides important baseline data for future reference in monitoring bat population status and conservation efforts in the region. Given the close relationship between the local people and bats (e.g. hunting and consumption), more work is needed to address the potential pathogen risks from zoonotic transmission, both from bats and the respective ectoparasites.